(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2017)
The so-called ‘neuro-psychological approach’ to aesthetics studies aesthetic perception and evaluation in neural, psychological, and social terms. All the empirical results recently collected by this approach are in line with the notion of ‘hermeneutic circle’. In particular, they suggest that aesthetic perception involves a special and original integration and coordination of low-level and high-level processing dynamics, top-down control and bottom-up construction of stimuli, and immediate and extensive evaluative processes.